A Case Report: Progressive Headache in a Rare Case a Meningioma: A Case Report - Feda Anisah Makkiyah; Nia Citama Saragih; Rosita Alfi Syahrin; Theodora Caroline Sihotang (Journal of Diverse Medical Research : Medicosphere, 2025)
The most prevalent primary tumor of the central nervous system is meningioma, and the incidence increases with age. This tumour can be detected through radiological examination and can be classified based on the results of anatomical pathology examination. A 48-year-old woman presented to the hospital with complaints of left-sided progressive headache since several years ago without any other complaints. Imaging examination showed a lesion in the falx cerebri of the sinistra aspect that suggested atypical meningioma. The woman decided to undergo craniotomy resection surgery and histopathological analysis. Based on the WHO classification, the histopathology results revealed that it was a micro and chordoidal meningioma. The patient had significant improvement in her symptoms postoperatively and the tumour size decreased on follow-up imaging. This case report demonstrates the importance of education about dangerous tumour headaches.